Effect of water absorption behaviour on tensile properties of hybrid jute-roselle woven fibre reinforced polyester composites - Hadi, A. E.; Tezara, C.; Fitriyana, D. F.; Siregar, J. P.; Oumer, A. N.; Hamdan, M. H. M.; Jaafar, J.; Zalinawati, M.; Irawan, A. P. (Penerbit Universiti Malaysia Pahang, 2021)
Incorporating natural fibre as reinforcement in the polymer matrix has shown a negative effect since the natural fibre is hydrophilic. The natural fibre easily absorbs water which causes an effect on the mechanical properties of the composites. The objective of this paper is to investigate the water absorption behaviour of hybrid jute-roselle woven fibre reinforced unsaturated polyester composite and the effect of water absorption in terms of tensile strength and tensile modulus. The effect of hybrid composite on the thickness swelling will be tested. The fabrication method used in this study is the hand lay-up technique to fabricate 2-layer and 3-layer composites with layering sequences of woven jute (J)/roselle (Ro) fibre. The results of the study showed that pure roselle fibres for 2 and 3-layer composites have the highest water absorption behaviour 3.86% and 5.51%, respectively, in 28 days) as well as thickness swelling effect, whereas hybrid J-Ro and J-J-Ro composites showed the least water absorption (2.65% and 3.76%, respectively) in 28 days) in both the tests. The hybridisation between jute and roselle fibres reduced water absorption behaviour and improved the fibres dimensional stability. The entire composites showed a decreasing trend for both tensile strength and tensile modulus strength after five weeks of water immersion. Jute fibre composite hybridised with roselle fibre can be used to reduce the total reduction of both tensile strength and tensile modulus throughout the whole immersion period. Moreover, the tensile testing showed that jute fibre composite hybridised with roselle fibre have produced the strongest composite with the highest tensile and modulus strength compared to other types of composites. The hybridisation of diverse fibre reinforcements aids in minimising the composite water absorption and thickness swelling, hence reducing the effect of tensile characteristics.